2018
DOI: 10.1111/ppa.12918
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of fosetyl‐Al, ethyl‐phosphite and phosphite against Pseudomonas syringae on plant surfaces and in vitro

Abstract: Fosetyl‐Al (the aluminium salt of ethyl‐phosphite) is an acid product used to fight oomycete diseases and sometimes used against bacterial diseases, but its antibacterial mode of action is largely unknown. Therefore, the direct effects of fosetyl‐Al and neutralized fosetyl‐Al on the colonization of leaf surfaces by Pseudomonas syringae were compared. Control of colonization was highest and almost complete in acidic conditions (99.7%), showing the importance of acidity for maximal antibacterial efficacy on plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Phosphite could also induce plant defense mechanisms by releasing superoxide, causing death of infected cells, and enhancing the accumulation of phenolic compounds (DANIEL & GUEST 2006). Moreover, phosphite can inhibit pathogen growth, as demonstrated for a mutant of P. syringae resistant to the antibiotic rifampicin, Pseudomonas syringae Psp191R1 by BULTREYS et al (2018). The authors reported that phosphite had a strong effect on in vitro growth of the pathogen, as well as on bacterial growth on the leaf surfaces, with a high acidic effect.…”
Section: Discussionmentioning
confidence: 98%
“…Phosphite could also induce plant defense mechanisms by releasing superoxide, causing death of infected cells, and enhancing the accumulation of phenolic compounds (DANIEL & GUEST 2006). Moreover, phosphite can inhibit pathogen growth, as demonstrated for a mutant of P. syringae resistant to the antibiotic rifampicin, Pseudomonas syringae Psp191R1 by BULTREYS et al (2018). The authors reported that phosphite had a strong effect on in vitro growth of the pathogen, as well as on bacterial growth on the leaf surfaces, with a high acidic effect.…”
Section: Discussionmentioning
confidence: 98%
“…Studies focusing on mycorrhiza, which can sometimes be suppressive towards plant pathogens, 58 showed that root colonization can either be stimulated or suppressed by phosphonic acid 59–62 . It is likely that the compositions of root and leaf microbiomes are perturbed directly by the antimicrobial action of phosphonic acid, 63 or indirectly by defence and signalling pathways, 64 and perhaps via alterations in plant carbohydrate or amino acid exudates. Any of these mechanisms could influence the plant microbiome and thus indirectly pathogen population and colonization of plant tissues.…”
Section: How Does Phosphonic Acid Suppress Oomycete Pathogens?mentioning
confidence: 99%
“…Fosetyl-Al is a systemic fungicide that has been also applied against bacterial diseases. A recent work proposed the role of fosetyl-Al in the control of the colonization of pear and cherry leaf surfaces by Pseudomonas syringae [11] and for the control of the bacterial canker of kiwifruit caused by P. syringae pv. actinidiae (Brunetti and Pilotti, personal communication).…”
Section: Phytopathogens Control Strategies: the Cases Of Xylella Fastmentioning
confidence: 99%